The Interface between Methyltransferase and Polymerase of NS5 Is Essential for Flavivirus Replication - Li, Xiao-Dan (Public Library of Science, 2014)
The flavivirus NS5 harbors both a methyltransferase (MTase) and an RNA-dependent RNA polymerase (RdRP). Both enzyme activities of NS5 are critical for viral replication. Recently, the full-length NS5 crystal structure of Japanese encephalitis virus reveals a conserved MTase-RdRP interface that features two conserved components: a six-residue hydrophobic network and a GTR sequence. Here we showed for the first time that these key interface components are essential for flavivirus replication by various reverse genetics approaches. Interestingly, some replication-impaired variants generated a common compensatory NS5 mutation outside the interface (L322F), providing novel routes to further explore the crosstalk between MTase and RdRP.